The Role of HIF-1α in Gingival Hypoxia Induced by Smoking: A Scoping Review - Mutiara Yulina Putri; Siti Sopiatin; Amaliya Amaliya (The ASEAN Journal of Military and Preventive Medicine, 2026)
Background: Smoking is a well-established risk factor for periodontal disease, primarily due to its role in inducing hypoxia within gingival tissues. Hypoxia, defined as reduced oxygen supply, disrupts normal tissue homeostasis, exacerbates inflammation, and impairs healing. Chronic exposure to smoking-related toxins leads to microvascular dysfunction, reduced oxygen delivery, and an upregulation of hypoxia-inducible factor-1 alpha (HIF-1α). This molecular adaptation is associated with increased apoptosis, impaired angiogenesis, and delayed periodontal tissue regeneration, all of which contribute to disease progression. Understanding the role of hypoxia in smoking-related periodontal destruction is crucial for developing targeted therapeutic interventions. Methods: This scoping review followed the Joanna Briggs Institute (JBI) protocol and PRISMA-ScR guidelines. A comprehensive search was performed in PubMed, EBSCOhost, Scopus, ScienceDirect, Google Scholar, and Web of Science using Boolean operators related to hypoxia, gingival health, and smoking. The Population-Concept-Context (PCC) framework guided the eligibility criteria, including observational and experimental studies that compared smokers and non-smokers. Extracted data included study design, sample size, periodontal parameters, and molecular findings. Results: Out of 265 screened articles, 11 met the inclusion criteria. These included experimental, cross-sectional, cohort, and randomized controlled trial (RCT) studies involving 473 participants. Results demonstrated that smokers exhibited significantly higher levels of HIF-1α, VEGF, and inflammatory markers in periodontal tissues compared to non-smokers. Smoking-induced hypoxia disrupted angiogenesis, increased osteoclastogenesis, and altered vascularization, contributing to delayed healing and periodontal tissue degradation. Some studies reported no synergistic effect between smoking and periodontitis on HIF-1α expression; however, smoking independently impacted hypoxia-related pathways. Conclusion and Implications: Smoking significantly contributes to periodontal disease by inducing hypoxia, disrupting angiogenic and inflammatory pathways, and impairing tissue regeneration. The upregulation of HIF-1α plays a central role in these mechanisms. Given these findings, integrating smoking cessation into periodontal management is essential. Future research should explore targeted interventions modulating HIF-1α activity to mitigate smoking-induced periodontal damage and improve treatment outcomes.